Debut of an endangered bird in zoos raises public interest, awareness and conservation knowledge of the species. (13th April 2021) - Fukano, Y.; Soga, M.; Fukuda, M.; Takahashi, Y.; Koyama, M.; Arakawa, Y.; Miyano, N.; Akiba, Y.; Horiguchi, M.
Abstract: Raising public awareness and support for endangered species is critical for global biodiversity conservation. However, we know little about which factors drive public interest in wildlife and how an increase in people's interest shapes their behaviours towards wildlife conservation. The animal debut of ex situ endangered species at zoos may raise general public interest in the conservation of these species. We assessed the impact of an animal debut using a case study of ex situ‐ bred Japanese rock ptarmigan, a bird subspecies locally endangered in Japan, on people's awareness, knowledge and behaviours regarding Japanese ptarmigan conservation. The public's reactions to ptarmigans were measured by using an online questionnaire survey and online sources of information (Google Trends, Wikipedia, Twitter and the donation website visits). The animal debut events generated a nationwide increase in information‐seeking and sharing behaviours on the web and in conservation‐oriented behaviour (measured by the number of donation website page visits). A significant increase in knowledge of ptarmigans was evident only among people living in prefectures where ptarmigans occurred. Overall, our results suggest that the debut of ex situ‐ bred endangered animals has the potential to promote public awareness, knowledge and behaviours for their conservation on a nationwide scale. Policy makers and practitioners should view zoos as important conservation centres and encourage conservation agencies to collaborate with them to reinforce public support for conservation programmes. Abstract : We assessed the impact of an animal debut of ex situ‐bred Japanese rock ptarmigan on people's awareness, knowledge and behaviours regarding Japanese ptarmigan conservation. The animal debut events generated a nationwide increase in information‐seeking and sharing behaviours on the web and in conservation‐oriented behaviour. Policy makers and practitioners should view zoos as important conservation centres.